Attitudes of Various Professional Groups towards the Use of Artificial Intelligence in the Migrant Recruitment Procedure - Bartkowiak, Grażyna; Krugiełka, Agnieszka (Postawy różnych grup zawodowych wobec wykorzystania sztucznej inteligencji w procedurze rekrutacji migrantów, 2025)
Aim: This article analyzes the attitudes of various professional groups toward using artificial intelligence (AI) in migrant recruitment. It includes a theoretical section discussing the need to employ migrants, the role of AI in recruitment, and the concept of attitudes as drivers of human behavior, as well as an empirical section presenting workshop-based research findings. Methodology: Interviews were conducted with three professional groups – academic teachers, HR specialists, and entrepreneurs (seven participants each) – to explore their views on AI’s usefulness in migrant recruitment. Results: The findings indicate generally positive attitudes across all groups toward using AI in this context. Implications: While no major differences were found between the groups, each highlighted different practical challenges in implementing AI. The study reveals a general openness to AI and outlines practical considerations for its application in recruitment. Originality/value: The article presents original research contributing to the development of knowledge on improving migrant recruitment processes through AI.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2025; vol. 69, nr 2, s. 1-11